2010
DOI: 10.1080/17451001003670086
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and temperature effects on osmoregulation by the invasive prawnPalaemon elegansRathke, 1837 in the Baltic Sea

Abstract: The effect of season and acclimation temperature on the osmoregulatory ability of the invasive prawn Palaemon elegans in the Baltic Sea was investigated. There was a significant seasonal effect that could be attributed largely to temperature. Decreasing environmental temperature increased haemolymph osmolality (i.e. improved osmoregulatory ability) in fieldsampled hyper-regulating prawns. This effect of temperature was confirmed in the laboratory for individuals acclimated to different salinity and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This feature, along with a considerable flexibility and opportunistic feeding in adults (Janas and Barańska 2008) and high tolerance of environmental factors like temperature and salinity (Janas and Spicer 2010), has enabled this species to colonize the coastal waters of the southern Baltic rapidly on a very large scale. Year-on-year studies carried out in VL have shown that the density of these animals, initially not very great (2005), has increased substantially (Ezhova 2009, Janas andBruska 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature, along with a considerable flexibility and opportunistic feeding in adults (Janas and Barańska 2008) and high tolerance of environmental factors like temperature and salinity (Janas and Spicer 2010), has enabled this species to colonize the coastal waters of the southern Baltic rapidly on a very large scale. Year-on-year studies carried out in VL have shown that the density of these animals, initially not very great (2005), has increased substantially (Ezhova 2009, Janas andBruska 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Low salinities in combination with extreme temperatures can also adversely affect prawns. It has been demonstrated that adults of P. elegans from the Baltic Sea are good hyperosmoregulators in brackish waters (Janas and Spicer 2010), but also that the osmoregulatory ability weakens at salinities <3 PSU at high (22°C) and low temperatures (2ºC) (Janas and Spicer 2010, Piłka et al in prep). Low salinity was cited as the main reason for the smaller size of Crangon crangon in its Baltic Sea populations (Muus 1967) and of bivalves such as Mya arenaria and Mytilus edulis (Robertson 1989, Kautsky andTendengren 1992).…”
Section: Discussionmentioning
confidence: 99%